Hotel's internal image level as an indicator of hospitality activity ("Journal "U". Economy. Management. Finance.", 2023)
The work raises the question of the importance of corporate image as the most important tool to increase the competitiveness of hotel enterprises. The need to consolidate the company's position in the modern market through strengthening the responsibility of each employee for the results of their activities is revealed. Taking into account the peculiarities of hotel activity, the structure of the image is revealed on the basis of its orientation, the indicators of the internal image of the hotel are determined. Using various research methods, the level of internal image of the hotel was measured and assessed. The greatest importance of certain factors has been confirmed, the priority tasks of the company's managers in this direction have been established.
Keywords: hotel; external and internal image; service quality indicators; structure of factors; survey method; observation method; consumer opinions; consumer satisfaction level; perception and expectation factor; negative reaction; positive emotions; organization image level; image hierarchy method; awareness availability